(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
Animal feed is a product of vegetable, animal or mineral origin, obtained naturally or in industrial process,as feed mixtures, concentrates and raw materials for the production of animal feed, which serve as food for animals, which are not harmful to their health.The animal feed can be processed,partly processed or unprocessed for animal nutrition. Historically, feed costs have represented 65 -75 percent of the variable costs of swine production, but for many producers this figure is higher now. As a result, feed costs play a major role in determining the profitability of a swine enterprise. Feed costs are, and will continue to be, an ever increasing factor in determining the profitability of a swine enterprise. Adopting ingredient alternatives seems like a logical step for pork producers. The aim of this study is to compare the qualitative parameters of feed stuffs from different groups,traditional and alternative,point to their advantages and their disadvantages by their usage during the process of animal breeding and livestock production,and all that in order to prove that the traditional feedstuffs can be replaced with alternative,which will cost effectively and provide variety of benefits to the swine ratio including energy,protein and fiber. The samples which were analysed were samples of corn and barley.The analyses were made in the labotory of the Agro Idustrial Association – AGRIA.Parameters which refer to the quality of the feedstuff and which were analysed were :moisture, ash insoluble in hydrochloric acid, raw proteins, raw fiber, acidity degree and the amount of substances that they shouldn?t contain or should contain only in certain quantities (forbidden substances).The obtained results were compared to the standard parameters in order to compare the quality of the analysed feedstuffs. The obtained values from the the tested samples are: moisture 10.4% and 10.58% for corn and barley respectively, proteins 8.06% and 11.27%; ash 1, 16% and 2.57%, fiber 2.61% and 3.84.